PVP-doped PVP-Ca0. 24V2O5H2O electrode material, preparation method thereof and application of PVP-doped PVP-Ca0. 24V2O5H2O electrode material in aqueous zinc ion battery

By introducing PVP into the cathode material of zinc ion batteries, PVP-Ca0.24V2O5·H2O electrode material was prepared, which solved the problems of poor conductivity and limited circulation performance of existing materials, and achieved significant improvement in the conductivity and circulation performance of the materials, and was suitable for the application of aqueous zinc ion batteries.

CN119833599AActive Publication Date: 2025-04-15ANHUI ZHONGRUI INFORMATION TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411932168.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The cathode materials of existing rechargeable zinc ion batteries have problems such as poor conductivity, poor rate performance and limited circulation performance, which hinder the development of their commercialization path.

Method used

Using PVP-doped PVP-Ca0.24V2O5·H2O electrode material, an electrode material with improved conductivity and cyclic properties was prepared by stirring vanadium pentoxide and calcium hydroxide in deionized water, adding polyvinylpyrrolidone (PVP), and then carrying out hydrothermal reaction.

Benefits of technology

It significantly improves the conductivity and cyclic performance of the material, reduces internal resistance, improves specific capacity and rate performance, has the characteristics of low cost, environmentally friendly, and high safety, and improves energy density and power density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833599A_ABST
    Figure CN119833599A_ABST
Patent Text Reader

Abstract

The invention discloses a PVP (Polyvinyl Pyrrolidone) doped PVP-Ca0. 24V2O5.H2O electrode material, a preparation method of the PVP doped PVP-Ca0. 24V2O5.H2O electrode material and application of the PVP doped PVP-Ca0. 24V2O5.H2O electrode The preparation method comprises the following steps: adding V2O5 and Ca (OH) 2 into deionized water, adding PVP into an obtained mixed solution, and continuously stirring; and transferring the obtained mixed solution into a stainless steel hydrothermal reaction kettle with a polytetrafluoroethylene lining, carrying out hydrothermal reaction, cooling to room temperature, carrying out centrifugal cleaning, and carrying out vacuum drying to obtain the PVP-doped PVP-Ca0. 24V2O5.H2O nanorod. According to the invention, PVP is doped in CaV6O16. 3H2O in the PVP-doped electrode material to form PVP-Ca0. 24V2O5.H2O with phase transition and doped PVP, so that ion diffusion and charge transfer are effectively promoted, the conductivity of the material is improved, the internal resistance of the material is reduced, the structural flexibility and stability of the material are maintained, and the overall performance of the aqueous zinc ion battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of materials, and specifically relates to a PVP-doped PVP-Ca 0.24 V2O5·H2O electrode material, preparation method thereof and application in aqueous zinc ion batteries. Background Art

[0002] As a new secondary clean and renewable energy source, lithium-ion batteries have the advantages of high operating voltage, light weight, and high energy density. They have been widely used in power tools, digital cameras, mobile phones, laptops and other fields. However, the production cost of lithium-ion batteries is high, the resource reserves of lithium are insufficient, and most of them use toxic and flammable organic electrolytes, which pose safety hazards and easily cause environmental pollution. These problems have seriously hindered their development and application in the field of large-scale energy storage.

[0003] Among these systems, aqueous rechargeable zinc-ion batteries have been proposed as viable alternatives due to their high abundance, low cost, large theoretical capacity (819 mAh / g), low redox potential (-0.763 V vs standard hydrogen electrode), high ionic conductivity of aqueous electrolyte (≈1.0 S / cm), high safety level, and environmental friendliness. However, the search for viable cathode materials remains a major obstacle on the road to commercialization of rechargeable zinc-ion batteries. Among the various rechargeable zinc-ion positive electrode materials, electrode materials such as manganese oxides and Prussian blue compounds are used. These materials have problems such as inevitable dissolution and unsatisfactory reversibility, resulting in poor conductivity, poor rate performance, and limited cycling performance. However, layered vanadium-based oxides have attracted widespread attention due to their open framework structure, rich valence states, and a variety of oxygen coordination polyhedra and bonding modes. These structural advantages provide a variety of redox reactions and adjustable interlayer spacing and tunnel sizes to accommodate efficient Zn 2+ storage, while achieving satisfactory reaction kinetics, the multiple valence states of vanadium and a diverse open framework make it one of the most promising materials. Summary of the invention

[0004] In order to solve the above-mentioned technical problems, one of the purposes of the present invention is to provide a PVP-doped PVP-Ca 0.24 V2O5·H2O electrode material and preparation method thereof.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a PVP-doped PVP-Ca 0.24 The V2O5·H2O electrode material, the preparation method thereof comprises the following steps:

[0006] Vanadium pentoxide (V2O5) and calcium hydroxide (Ca(OH)2) were added to deionized water and stirred at 70-80°C for 3-4 hours; then, polyvinyl pyrrolidone (PVP) was added to the obtained mixed solution and stirred for 30-40 minutes; the obtained mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for hydrothermal reaction, cooled to room temperature, centrifuged and washed, and vacuum dried to obtain PVP-Ca doped with PVP. 0.24 V2O5·H2O

[0007] Preferably, the above-mentioned PVP-doped PVP-Ca 0.24 V2O5·H2O electrode material, by mass ratio, vanadium pentoxide: calcium hydroxide: polyvinyl pyrrolidone = 1.00: 0.20: 0.04-0.30.

[0008] Preferably, the above-mentioned PVP-doped PVP-Ca 0.24 V2O5·H2O electrode material, the hydrothermal reaction is to transfer the obtained mixed solution to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and react at 175-185°C for 24-25h.

[0009] The second object of the present invention is to provide the above-mentioned PVP-doped PVP-Ca 0.24 Application of V2O5·H2O electrode material as positive electrode in aqueous zinc ion batteries.

[0010] Preferably, the above application method comprises the following steps:

[0011] 1) Preparation of positive electrode: PVP-doped PVP-Ca 0.24 After the V2O5·H2O electrode material is mixed evenly with the binder and the conductive material, a small amount of N-methylpyrrolidone solution (NMP) is added as a solvent. After mixing evenly, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain PVP-Ca coated with PVP. 0.24 V2O5·H2O positive electrode;

[0012] 2) Preparation of negative electrode sheet: A zinc sheet with a thickness of 0.1 mm to 0.3 mm and a purity of 99% to 99.99% is polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet is cut into a circle with a diameter of 12 mm as a negative electrode sheet;

[0013] 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and the electrolyte is 2M zinc trifluoromethanesulfonate to obtain an aqueous zinc ion battery.

[0014] Preferably, in the above application, in step 1), the binder is polyvinylidene fluoride (PVDF).

[0015] Preferably, in the above application, in step 1), the conductive material is Super-p.

[0016] Preferably, in the above application, by weight ratio, PVP-Ca doped with PVP 0.24 V2O5·H2O electrode material: conductive material: binder = 7:2:1.

[0017] The beneficial effects of the present invention are:

[0018] 1. The present invention significantly improves the conductivity and cycle performance of the material and reduces the internal resistance by introducing PVP during the synthesis process.

[0019] 2. In the present invention, the introduction of PVP causes a phase transition and changes the interlayer spacing, thereby improving the specific capacity and rate performance of the material during the charge and discharge process.

[0020] 3. The present invention has the characteristics of low cost, environmental friendliness and high safety.

[0021] 4. The present invention has higher energy density and power density.

[0022] 5. The present invention has simple synthesis and assembly processes, is easy to operate and control, and is suitable for continuous large-scale production.

[0023] 6. In the present invention, after modification, the capacity of the electrode material is increased from 120 mAh / g to 170 mAh / g.

[0024] 7. The method provided by the present invention is also applicable to other metal vanadate positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The CaV6O prepared in Example 1 16 ·3H2O and PVP doped PVP-Ca 0.24 XRD spectrum of V2O5·H2O.

[0026] Figure 2 The PVP-Ca doped with PVP prepared in Example 1 0.24 SEM spectrum of V2O5·H2O.

[0027] Figure 3 The CaV6O prepared in Example 1 16 ·3H2O and PVP doped PVP-Ca 0.24 Cyclic voltammogram of V2O5·H2O.

[0028] Figure 4 The CaV6O prepared in Example 116 ·3H2O and PVP doped PVP-Ca 0.24 Specific capacity diagram of V2O5·H2O. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0030] Example 1

[0031] (I) CaV6O 16 The preparation method of 3H2O is as follows:

[0032] 0.728 g of V2O5 and 0.148 g of Ca(OH)2 were added to 80 mL of deionized water. The above solution was stirred at 70 °C for 3 h, and the resulting mixed solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and kept at 180 °C for 24 h. The resulting product was washed several times with deionized water and ethanol, and the obtained dark red product was dried in a vacuum oven at 60 °C for 12 h to obtain CaV6O 16 ·3H2O nanorods.

[0033] (ii) PVP-Ca doped with PVP 0.24 The preparation method of V2O5·H2O is as follows:

[0034] 0.728 g of V2O5 and 0.148 g of Ca(OH)2 were added to 80 mL of deionized water. The above solution was stirred at 70 °C for 3 h. Then, 100 mg of PVP was added to the resulting yellow solution and stirred for 30 min. The resulting mixed solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and kept at 180 °C for 24 h. The resulting product was washed several times with deionized water and ethanol, and the obtained dark green product was dried in a vacuum oven at 60 °C for 12 h to obtain PVP-Ca doped with PVP. 0.24 V2O5·H2O nanorods.

[0035] (III) Detection

[0036] Figure 1 The CaV6O prepared in this example 16 ·3H2O and PVP doped PVP-Ca 0.24 XRD spectrum of V2O5·H2O. Figure 1 It can be seen that after PVP doping, the XRD spectrum of the sample showed obvious changes, indicating that PVP was successfully doped into CaV6O 16·3H2O and a phase transformation to Ca 0.24 V2O5·H2O.

[0037] Figure 2 It is PVP-Ca doped with PVP 0.24 SEM spectrum of V2O5·H2O. Figure 2 It can be seen that the prepared PVP-doped PVP-Ca 0.24 V2O5·H2O has a typical rod-like structure.

[0038] Figure 3 It is CaV6O 16 ·3H2O and PVP doped PVP-Ca 0.24 Cyclic voltammetry curve of V2O5·H2O. Figure 3 It can be seen that PVP-Ca 0.24 The area enclosed by V2O5·H2O is significantly larger than that of pure CaV6O 16 ·3H2O, which indicates that PVP-doped PVP-Ca 0.24 The capacity of V2O5·H2O is greater than that of pure CaV6O 16 ·3H2O.

[0039] Figure 4 It is CaV6O 16 ·3H2O and PVP doped PVP-Ca 0.24 Specific capacity diagram of V2O5·H2O. Figure 4 It can be seen that PVP-Ca 0.24 The specific capacity and cycle stability of V2O5·H2O are much higher than those of pure CaV6O 16 ·3H2O.

[0040] Example 2

[0041] PVP-doped PVP-Ca 0.24 The preparation method of V2O5·H2O is as follows

[0042] 0.728 g of V2O5 and 0.148 g of Ca(OH)2 were added to 80 mL of deionized water, and the solution was stirred at 70 °C for 3 h. Then, 30 mg of PVP was added to the yellow solution and stirred for 30 min. The mixed solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and kept at 180 °C for 24 h. The obtained product was washed several times with deionized water and ethanol, and the obtained dark green product was dried in a vacuum oven at 60 °C for 12 h to obtain PVP-Ca doped with PVP. 0.24 V2O5·H2O nanorods.

[0043] Example 3

[0044] PVP-doped PVP-Ca 0.24 The preparation method of V2O5·H2O is as follows

[0045] 0.728 g of V2O5 and 0.148 g of Ca(OH)2 were added to 80 mL of deionized water, and the solution was stirred at 70 °C for 3 h. Then, 50 mg of PVP was added to the yellow solution and stirred for 30 min. The mixed solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and kept at 180 °C for 24 h. The obtained product was washed several times with deionized water and ethanol, and the obtained dark green product was dried in a vacuum oven at 60 °C for 12 h to obtain PVP-Ca doped with PVP. 0.24 V2O5·H2O nanorods.

[0046] Example 4

[0047] PVP-doped PVP-Ca 0.24 The preparation method of V2O5·H2O is as follows

[0048] 0.728 g of V2O5 and 0.148 g of Ca(OH)2 were added to 80 mL of deionized water, and the solution was stirred at 70 °C for 3 h. Then, 200 mg of PVP was added to the yellow solution and stirred for 30 min. The mixed solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and kept at 180 °C for 24 h. The obtained product was washed several times with deionized water and ethanol, and the obtained dark green product was dried in a vacuum oven at 60 °C for 12 h to obtain PVP-Ca doped with PVP. 0.24 V2O5·H2O nanorods.

[0049] Example 5 Preparation of aqueous zinc ion battery

[0050] 1) Preparation of positive electrode sheet: PVP-Ca doped with PVP prepared in Example 1 0.24 After the V2O5·H2O electrode material is mixed with Super-p and PVDF in a mass ratio of 7:2:1, a small amount of NMP is added as a solvent, and after mixing evenly, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven for drying, and then taken out to obtain PVP-doped PVP-Ca 0.24 V2O5·H2O positive electrode, spare;

[0051] 2) Preparation of negative electrode sheet: A zinc sheet with a thickness of 0.3 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into small discs with a diameter of 12 mm as negative electrode sheets for later use;

[0052] 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and 2M zinc trifluoromethanesulfonate is selected as the electrolyte to obtain an aqueous zinc ion battery.

[0053] Example 6 Preparation of aqueous zinc ion battery

[0054] 1) Preparation of positive electrode sheet: PVP-Ca doped with PVP prepared in Example 2 0.24 After the V2O5·H2O electrode material is mixed with Super-p and PVDF in a mass ratio of 7:2:1, a small amount of NMP is added as a solvent, and after mixing evenly, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven for drying, and then taken out to obtain PVP-doped PVP-Ca 0.24 V2O5·H2O positive electrode, spare;

[0055] 2) Preparation of negative electrode sheet: A zinc sheet with a thickness of 0.3 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into small discs with a diameter of 12 mm as negative electrode sheets for later use;

[0056] 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and 2M zinc trifluoromethanesulfonate is selected as the electrolyte to obtain an aqueous zinc ion battery.

[0057] Example 7 Preparation of Aqueous Zinc Ion Battery

[0058] 1) Preparation of positive electrode sheet: PVP-Ca doped with PVP prepared in Example 3 0.24 After the V2O5·H2O electrode material is mixed with Super-p and PVDF in a mass ratio of 7:2:1, a small amount of NMP is added as a solvent, and after mixing evenly, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven for drying, and then taken out to obtain PVP-doped PVP-Ca 0.24 V2O5·H2O positive electrode, spare;

[0059] 2) Preparation of negative electrode sheet: A zinc sheet with a thickness of 0.3 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into small discs with a diameter of 12 mm as negative electrode sheets for later use;

[0060] 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and 2M zinc trifluoromethanesulfonate is selected as the electrolyte to obtain an aqueous zinc ion battery.

[0061] Example 8 Preparation of Aqueous Zinc Ion Battery

[0062] 1) Preparation of positive electrode sheet: PVP-Ca doped with PVP prepared in Example 4 0.24 After the V2O5·H2O electrode material is mixed with Super-p and PVDF in a mass ratio of 7:2:1, a small amount of NMP is added as a solvent, and after mixing evenly, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven, and dried and taken out to obtain PVP-Ca coated with PVP doping. 0.24 V2O5·H2O positive electrode, spare;

[0063] 2) Preparation of negative electrode sheet: A zinc sheet with a thickness of 0.3 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into small discs with a diameter of 12 mm as negative electrode sheets for later use;

[0064] 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and 2M zinc trifluoromethanesulfonate is selected as the electrolyte to obtain an aqueous zinc ion battery.

[0065] The four aqueous zinc ion batteries assembled in Examples 5 to 8 were subjected to electrochemical tests. We found that Example 5 had the best electrochemical performance, with a long cycle life of 2700 cycles at a current density of 10 A / g and a capacity retention rate of 80.1% (e.g. Figure 4 As shown in Example 5, the mass ratio of vanadium pentoxide: calcium hydroxide: polyvinyl pyrrolidone is 1:0.2:0.13. The PVP-doped PVP-Ca 0.24 The V2O5·H2O nanorods undergo a phase transition and become more uniformly ordered in size, providing more active sites, making it easier to store more zinc ions. They also promote the embedding and extraction of zinc ions, thereby improving their electrochemical performance.

Claims

1. A PVP-doped PVP-Ca 0.24 V2O5·H2O electrode material, characterized in that The preparation method comprises the following steps: V2O5 and Ca(OH)2 were added to deionized water and stirred at 70-80°C for 3-4h; then, polyvinylpyrrolidone (PVP) was added to the obtained mixed solution and stirred for 30-40min; the obtained mixed solution was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for hydrothermal reaction, cooled to room temperature, centrifuged and washed, and vacuum dried to obtain PVP-Ca doped with PVP. 0.24 V2O5·H2O.

2. A PVP-Ca doped with PVP according to claim 1 0.24 V2O5·H2O electrode material, characterized in that In terms of mass ratio, V2O5:Ca(OH)2:polyvinylpyrrolidone=1.00:0.20:0.04~0.

30.

3. A PVP-Ca doped with PVP according to claim 1 0.24 V2O5·H2O electrode material, characterized in that The hydrothermal reaction is to transfer the obtained mixed solution to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene and react at 175-185° C. for 24-25 hours.

4. A PVP-doped PVP-Ca according to any one of claims 1 to 3 0.24 Application of V2O5·H2O electrode material as positive electrode in aqueous zinc ion batteries.

5. The use according to claim 4, characterized in that: The method for preparing the positive electrode sheet comprises the following steps: PVP-doped PVP-Ca 0.24 After the V2O5·H2O electrode material is mixed evenly with the binder and the conductive material, a small amount of NMP is added as a solvent. After mixing evenly, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain the PVP-Ca coated with PVP. 0.24 The positive electrode of V2O5·H2O.

6. The use according to claim 5, characterized in that: The binder is PVDF.

7. The use according to claim 5, characterized in that: The conductive material is Super-p.

8. The use according to claim 5, characterized in that: According to the mass ratio, PVP-doped PVP-Ca 0.24 V2O5·H2O electrode material: conductive material: binder = 7:2:1.

Citation Information

Patent Citations

  • Preparation method and application of double-ion doped vanadium pentoxide positive electrode material

    CN110364726A

  • High-performance water system zinc ion battery anode material, manufacturing method and application thereof

    CN110474044A

  • Metal vanadate nanocomposite material and preparation method thereof, and lithium ion secondary battery

    CN113816422A

  • PVP (Polyvinyl Pyrrolidone) modified MnVOx electrode material, preparation method and application of PVP modified MnVOx electrode material in zinc ion battery

    CN115513450A

  • Method for preparing fibrous zinc ion pre-intercalated hydrated vanadium pentoxide and application of fibrous zinc ion pre-intercalated hydrated vanadium pentoxide in zinc ion battery

    CN117985757A